INSURANCE INTERMEDIARIES’ WORK-RELATED STRESS: CONNECTIONS WITH LABOUR PRODUCTIVITY - Kulvinskienė, Violeta Raimonda; Apčelauskaitė, Gintarė (Ekonomika, 2014)
Abstract. The article deals with work-related stress, the reasons for its occurrence, consequences, and ways how to manage stress in the Lithuanian “X” life insurance company. The intermediaries’ work stress connection with labour productivity and type A personality behaviour are analyzed. The study aims to find out how the insurance company takes certain measures to minimize work-related stress and to increase labour productivity. Key words: work-related stress, labour productivity, Type A character behaviour, work-related stress management